Design 3D tiskárny - Chrástek, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Diplomová práce je zaměřena na design stereolitografické 3D tiskárny za použití nových technologií za účelem zvětšení pracovní plochy a snadného a pohodlného ovládání. Největší součástí práce je zaměření na tvarovou a estetickou stránku věci s ohledem na funkční, bezpečnostní, ergonomické a technické nároky, které by tento produkt měl splňovat.

Diploma thesis is focused on design of stereolithography 3D printer, which includes new technology and innovations to achive larger workspace and easy and comfortable manipulation. Great part of thesis is focused on shaping and aesthetic effect with respect of functional, safety, ergonomic and technical claims.
Design of 3D Printer
Keywords: Design; 3D tisk; stereolitografie; rapid prototyping; 3D technologie; koncept; Design; 3D print; stereolithography; rapid prototypung; 3D technology; concept